MODERN METHODS IN TEACHING ENGLISH FOR NON-PHILOLOGY UNIVERSITY STUDENTS - Gulnoz Abduxalilovna Kayumova (Western European Studies, 2024)
This article explores the importance of modern methods in effectively teaching English as a foreign language. It argues that educators should embrace innovative pedagogical technologies to cultivate a new generation of learners with strong social skills, independent thinking, and the ability to solve problems effectively. The article highlights the challenges educators face in adopting new methods and explores solutions to overcome these obstacles. It emphasizes the importance of creating a language learning environment and utilizing various communication techniques to enhance the learning experience
Keywords: Educator; method; innovation